Fixed Airflow Limitation in Severe Asthma: Rethinking the Role of Small Airway Disease - Miguel Jiménez-Gómez; Ismael García-Moguel; Rocío Magdalena Díaz-Campos (Open Respiratory Archives, 2025)
Small airway disease (SAD) remains a challenging and underrecognized driver of fixed airflow obstruction in severe asthma. Impulse oscillometry (IOS) provides valuable insight into peripheral airway dysfunction and allows characterization of different bronchodilator response patterns. We describe two cases of late-onset severe asthma with confirmed SAD by spirometry and IOS, unresponsive to systemic corticosteroids and to biologics, despite optimized high-dose extrafine triple inhaled therapy and adherence. Both patients exhibited persistent airflow obstruction and abnormal IOS parameters, suggesting a resistant SAD phenotype. Importantly, the role of corticosteroid challenge in this subgroup remains unclear, as it failed to predict subsequent biologic response. These observations highlight the clinical utility of IOS in diagnosing and monitoring SAD and reinforce the need for personalized therapeutic approaches to address this treatment-resistant endotype of severe asthma. Resumen: La enfermedad de la vía aérea pequeña constituye un componente difícil de diagnosticar en el asma grave con obstrucción grave. La oscilometría de impulsos (IOS) permite caracterizar la disfunción periférica y describir distintos patrones de respuesta broncodilatadora, aportando un fenotipado más preciso. Presentamos dos casos de asma grave de inicio tardío con afectación de vía pequeña confirmada por espirometría e IOS, refractarios a corticoides sistémicos y a biológicos, a pesar de tratamiento inhalado triple optimizado y buena adherencia. Ambos mostraron obstrucción persistente y parámetros oscilométricos alterados, sugiriendo un fenotipo resistente. Destacamos que el papel del reto con corticoides en este subgrupo de pacientes sigue siendo incierto, pues no predijo la respuesta posterior a biológicos. Estos hallazgos refuerzan el valor de la IOS en el diagnóstico y seguimiento de la afectación de vía aérea pequeña, y subrayan la necesidad de estrategias terapéuticas personalizadas.